Factors influencing successful bone union of isolated subtalar arthrodesis for posttraumatic subtalar arthritis: a multicenter case series - Hyong Nyun Kim; Young Rak Choi; Bom Soo Kim; Yu Mi Kim; Jaehyung Lee; Jae Ho Cho; Sunho Cha; Jae Yong Park (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background The purpose of this study was to find the factors influencing successful bone union for isolated subtalar arthrodesis in posttraumatic subtalar arthritis following calcaneal fracture. Material and methods We retrospectively analyzed the rate of successful bone union of 119 cases of isolated subtalar arthrodesis for posttraumatic subtalar arthritis performed at five university hospitals between January 2010 and December 2019. Multivariate logistic regression analysis was used to find the factors associated with successful bone union. Successful bone union was defined as resolution of hindfoot pain with the presence of osseous trabecular bridging involving more than 50% of the posterior facet within 6 months postoperatively. Results There were 77 (64.7%) cases of successful bone union, 11 (9.2%) cases of delayed union, 8 (6.7%) cases of questionable union, and 23 (19.3%) cases of nonunion. Use of fully threaded screws was 5.90 times [odds ratio (OR) = 5.90, 95% confidence interval (CI) = 1.42–24.49, p = 0.02] more likely to achieve successful bone union compared to the use of partially threaded screws. Use of two parallel screws or the two divergent screws were 3.71 times (OR = 3.71, 95% CI = 1.05–13.14, p = 0.04) and 4.65 times (OR = 4.65, 95% CI = 1.23–17.53, p = 0.02) more likely to achieve successful bone union compared to the use of a single screw. Use of cancellous autograft or structural autograft was 4.72 times (OR = 4.72, 95% CI = 1.17–19.06, p = 0.03) and 7.12 times (OR = 7.12, 95% CI = 1.46–34.68, p = 0.02) more likely to achieve successful bone union compared to no graft use. Conclusion Use of fully threaded screws, autograft, and two screws compared to a single screw were the factors associated with successful bone union within six postoperative months after subtalar arthrodesis for the posttraumatic arthritis.